Microglial TREM2 Mitigates Inflammatory Responses and Neuronal Apoptosis in Angiotensin II-Induced Hypertension in Middle-Aged Mice - Xu, Xiaotian; Du, Lin; Jiang, Jianxiong; Yang, Ming; Wang, Zhaoxia; Wang, Yingge; Tang, Tieyu; Fu, Xuetao; Hao, Jiukuan (Frontiers in Aging Neuroscience, 2021)
Growing evidence suggests that hypertension and aging are prominent risk factors in the development of late-onset AD (LOAD) by induce of neuroinflammation. Recent study showed that neuroinflammation via activated microglia induces reactive astrocytes, termed A1 astrocytes, that highly upregulate numerous classical complement cascade genes that are destructive to neurons in neurodegeneration diseases. Moreover, triggering receptor expressed on myeloid cells 2 (TREM2) is considered as one of the strongest single-allele genetic risk factors and plays important roles on neuroinflammation for LOAD. However, the mechanisms of microglia regulate A1 astrocytic activation are still not clear. We introduced angiotensin II-induced hypertension in middle-aged mice and found that hypertension upregulated TREM2 expression and A1 astrocytic activation were involved in neuroinflammation in the current animal model. Our results revealed that overexpression of microglial TREM2 not only mitigates microglial inflammatory response, but also has salutary effects on reverse A1 astrocytic activation and neuronal toxicity.